Hand-Scanning Ultrasound Mass Screening for Breast Cancer in Women Aged Under 50 - KUMAZAWA, Iwao; TSUCHIYA, Juji; HASHIMOTO, Hidehisa; KAWAGOE, Hajime; UNO, Takashi; NAWA, Masato; ASANO, Masayoshi; TACHIBANA, Susumu (JOURNAL OF THE JAPANESE ASSOCIATION OF RURAL MEDICINE, 2003)
A total of 82 cases of breast cancer detected by hand-scanning ultrasound massscreenig (hereafter referred to as US screening) over the past 15 years were divided into two groups--one aged under 50 and the other aged 50 or over at the time of examinaton. The accuracy and capacity of US screening and the rate of patients with subjective symptoms were studied for each group. As a result, we discovered that the groupaged under 50 was significantly higher in the rate of “further examination needed”, and the rate of “having subjective symptoms”, and was significantly lower in “positive predictivevalue” than the older age group. In the detection rate, sensitivity and specificity, there was no difference between the two groups. Thus, we concluded that US screening were beneficial to both groups. Dividing the 15 years of US screening into three periods (each 5 years), we investigated the caliber of detected breast cancers, and found the tumor size became smaller year after year. As a result, the cases of non-palpable breast cancer came to form 26.6%, of which 72.3% was accounted for by invasive breast cancer. Further more, we found that in the group aged under 50, because of stiffness of their breast gland, the ratio of non-palpable breast cancer came to 30.2%, which was larger than in the older age group, and 69.2% cases out of them were invasive breast cancer. We are afraid that mass-screening by physical examination alone will overlook many cases of breast cancer, and we recommend that in view of the increasing mortality rate of breast cancer in women in their50s the safe and useful US screening program should be implemented without delay on the younger age group.